The Effect of Problem Based Learning (Pbl) Model Using Nearpod Media on Students' Learning Outcomes In Class V of Elementary School Pkn Learning - Mustikarani, Tinon; Soepeno, Bambang; Bektiarso, Singgih (MSJ : Majority Science Journal, 2025)
Student learning outcomes are influenced by the PBL approach assisted by Nearpod media. This research methodology is quantitative with an experimental strategy. This study used a nonequivalent control group design pattern in a quasi-experimental research approach. Researchers chose this design in order to use Nearpod media to implement PBL principles. There are two groups, namely the control group that uses the learning model and classroom media as a comparison, and the experimental group that uses Nearpod media as a complement to the PBL paradigm. 50 fifth-grade children from Citrodiwangsan 2 Lumajang Elementary School made up the study's population. They were divided into two classes. There are 25 pupils in class 5A and 25 students in class 5B. Probability sampling combined with random sampling was the method used for sampling in this investigation. The three phases of the research process were the planning phase, the research implementation phase, and the research completion phase. Tests, observations, documentation, and interviews were the approaches used to acquire data for this study. Using the SPSS Version 26 software, the data analysis methods employed in this study included t-tests, homogeneity tests, and normality tests. The Kolmogorov-Smirnov test was used to perform the normalcy test. To ascertain the extent to which the PBL paradigm, aided by Nearpod media, impacted the Civics learning outcomes of grade V students at SD Citrodiwangsan 2 Lumajang, the Shomogeneity test using Leven's statistics, and the t-test employed the independent sample t-test.